Strategy for the Implementation of Credit Cooperation Management System Based Online Application to Increase the Income of Cooperative and Members - Agung Sudjatmoko; Febrizal Rahmana; Aini Farmania (Bina Nusantara University, 2019)
The application of business management systems and cooperative organizations faces the challenges of the development of business dynamics due to the development of science and technology. The use of information technology in all business actors is a form of adaptation to anticipate business development that aims to increase competitiveness and win competition. Cooperative is a business that still has obstacles in optimizing the use of IT to manage businesses in providing services to members. Therefore, through the use of the cooperative organization's business identification methods, the analysis of the guidelines for the use of cooperative online systems, training and outreach, and evaluating the implementation of activities. In this case, the community service activities can provide results that have an impact on optimizing the online cooperative system in improving services and incomes of members and cooperatives.